EVALUASI KINERJA PENYULUH PERTANIAN LAPANGAN DAN EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL DI BALAI PENYULUHAN PERTANIAN KECAMATAN LINGGANG BIGUNG KABUPATEN KUTAI BARAT (Performance Evaluation Of Agricultural Intentions And The Effectiveness Of Using Social Media In Agricultural Counseling Centers, Linggang Bigung Sub-District Kutai Barat Regency) - ELMASARI ELMASARI; NDAN IMANG; MARIYAH MARIYAH (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2023)
This study aims to examine the performance of agricultural agent and determine the effectiveness of using social media in agricultural agent. This research was conducted in March-May2022. The research location was at the Agricultural Extension Center, Linggang Bigung District, West Kutai Regency. The sampling method used a census technique for 11 agricultural agent and 27 farmers used a purposive sampling technique. Data analysis used the Likert Scale and Rank Spearman test. The results showed that the performance of agricultural agent was in the good category with an average score of 36.55 and the effectiveness of using social media was in the effective category with an average of 36.89, while the performance of agricultural agent and the effectiveness of using social media in agricultural extension services had a relationship which is not real, where ρ table = 0.618 and ρ count 0.300 means ρ count < ρ table means Ho is accepted and Ha is rejected. Agricultural agent have carried out their duties and functions well and it is hoped that in the future the use of social media will continue to be increased so that agricultural extension services will be more effective and efficient.